Knowledge dissemination approaches targeting women increase their use of climate-smart agricultural practices - Saran, Ashrita; Puskur, Ranjitha (CGIAR GENDER Impact Platform, 2023)
Women are more likely to adopt improved CSA approaches when they are involved in decision-making and have equal access to information and resources. The odds can be improved through knowledge dissemination approaches that target women farmers and ensure their participation, such as Farmer Field Schools and training by extension services. Interventions can successfully increase both women and men farmers’ knowledge and adoption of specific CSA practices. However, further research reporting gender-disaggregated data and gender analysis is needed to determine what approaches are more effective at increasing adoption by women farmers.